Engineering nitrogen and oxygen functionalities in naturally sourced activated carbon for multicomponent gas adsorption - Xiupeng Cheng; Zhipeng Qie; Huaizhong Xiang; Zhongbao Liu; Limingxin Zong; Wenqi He; Xinxin Pi; Hassan Alhassawi; Peiyao Cao; Guang Yang; Shuangshuang Gao (Scientific Reports)
Abstract Nitrogen doping is a widely adopted strategy to enhance the gas adsorption performance of activated carbon (AC) adsorbents. However, the simultaneous evolution of oxygen and nitrogen functional groups—especially in carbon precursors with high oxygen content—has received limited attention. In this study, coal-derived ACs with high surface areas (up to 940 m2/g) and micropore volumes (0.36 cm3/g) were synthesized via K2CO3-assisted physical activation, followed by nitrogen doping through co-pyrolysis with melamine. By regulating the doping temperature (600–900 °C), the nitrogen content of the resulting samples ranged from 1.44 to 7.68 at%, while the oxygen content varied from 6.89 to 10.39 at%. After decoupling the influences of porosity, we found that a well-balanced distribution of N and O functionalities, especially pyrrolic nitrogen, ether (C–O–C), and hydroxyl (C–O–H) groups, was critical for enhancing CO2 and H2O adsorption. NAC-600 exhibited the most favorable surface chemistry for the adsorption of CO2 (15 vol%) and H2O (20% RH), achieving capacities of 41 mg/g and 59.9 mg/g, respectively. In contrast, NAC-900, prepared at the highest N-doping temperature, exhibited the best surface chemistry for toluene adsorption (550 mg/cm3), attributed to its higher degree of graphitization and the presence of graphitic N and ether groups. This work offers a rational design strategy for improving the multicomponent gas adsorption performance of activated carbons for flue gas treatment.